2008
DOI: 10.1016/j.drugalcdep.2008.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol intake patterns in female mice: Influence of allopregnanolone and the inhibition of its synthesis

Abstract: The neurosteroid allopregnanolone (ALLO) is a positive modulator of GABA(A) receptors that exhibits a psychopharmacological profile similar to ethanol (i.e., anxiolytic, sedative-hypnotic). Based on research suggesting that manipulation of ALLO levels altered ethanol self-administration in male rodents, the current studies determined whether exogenous ALLO administration or the inhibition of its synthesis in vivo modulated ethanol intake patterns in female C57BL/6J mice. Lickometer circuits collected temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 89 publications
4
34
1
Order By: Relevance
“…In addition, we also utilized a saline-treated control group in both of the 5-day investigations using female mice (24-h-bottle-bottle-choice and DID studies), it is unlikely that the differences in 10E and 20E intake between the MOX and saline group could be attributed to the estrous cycle. This conclusion is similar to previous work where no systematic changes in ethanol intake across weeks of baseline consumption in female C57BL/6 mice were observed (Ford et al, 2008). Collectively, these results suggests that the estrous cycle is unlikely to have an impact on the anti-alcohol effects of MOX and further supports the utility of MOX as a pharmacotherapy for AUD in both male and female.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we also utilized a saline-treated control group in both of the 5-day investigations using female mice (24-h-bottle-bottle-choice and DID studies), it is unlikely that the differences in 10E and 20E intake between the MOX and saline group could be attributed to the estrous cycle. This conclusion is similar to previous work where no systematic changes in ethanol intake across weeks of baseline consumption in female C57BL/6 mice were observed (Ford et al, 2008). Collectively, these results suggests that the estrous cycle is unlikely to have an impact on the anti-alcohol effects of MOX and further supports the utility of MOX as a pharmacotherapy for AUD in both male and female.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that sensitivity to neuroactive steroids differs between genotypes in male B6 and D2 mice (Finn et al, 1997(Finn et al, , 2000, but this effect has not been investigated systematically in female animals. However, it has been shown that there is an increase in whole brain ALLO levels in male B6 mice in response to a voluntary drinking paradigm, while the same paradigm elicited no change in brain ALLO levels in female B6 mice (Finn et al, 2004b) and that injections of ALLO increased EtOH consumption in male B6 mice (Ford et al, 2005;Sinnott et al, 2002), but had no effect on consumption in female B6 mice (Ford et al, 2007). Taken together, these data suggest that female B6 mice may be relatively insensitive to neuroactive steroid modulation.…”
Section: Discussionmentioning
confidence: 66%
“…Recent work with ganaxolone, a synthetic derivative of ALLO that exhibits metabolic resistance, reported a similar bimodal influence of this neurosteroid on operant ethanol self-administration in male alcohol preferring (P) rats (Besheer et al 2010). Curiously, female C57BL/6J mice were unresponsive to these modulatory effects of ALLO on limited access drinking in a procedure identical to that reported for C57BL/6J males (Ford et al 2008a; also see Finn et al 2010). Second, treatment with finasteride dose-dependently attenuated the acquisition (Ford et al 2008b) and the maintenance (Ford et al 2005a) of limited access ethanol intake in male mice, but a much higher dose was required to decrease ethanol drinking in female mice.…”
Section: Introductionmentioning
confidence: 60%
“…Second, treatment with finasteride dose-dependently attenuated the acquisition (Ford et al 2008b) and the maintenance (Ford et al 2005a) of limited access ethanol intake in male mice, but a much higher dose was required to decrease ethanol drinking in female mice. It was notable that the finasteride-induced decrease in ethanol intake was due to a sex-specific mechanism of drinking pattern alteration (Ford et al 2005a, 2008a; also see Finn et al 2010). Third, ALLO and ganaxolone facilitated reinstatement of ethanol seeking (Finn et al 2008; Nie and Janak 2003; Ramaker et al 2014) and ALLO as well as other GABA A R-positive modulatory steroids, including pregnanolone and allotetrahydrodeoxycorticosterone, substituted for the discriminative stimulus effects of ethanol (Grant et al 1996, 1997; Bowen et al 1999; Hodge et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation